PERENCANAAN BISNIS KERAJINAN PERCA BATIK UNTUK UMKM - Titi Rahayu Prasetiani; Sri Puji Astuti; Catur Ragil Sutrisno (LPPM Universitas Pekalongan, 2020)
Pekalongan, also known as “Batik City” has a potential of batik craft development, especially by using waste of batik fabric. Such batik waste usually is sold directly with no added value. Small Scale Enterprises of Batik Craft should survive facing a tight business competition. So, it is important to have a business plan analysis in order to win in such competiton. The purposes of this research are : 1) to analysis production aspect of batik craft focusing on product development and process standardization, 2) to analysis of batik craft marketing, focusing on consumer analysis and market analysis. Thus research was done through value engineering descriptive analitical approaches,